1997
DOI: 10.1523/jneurosci.17-10-03932.1997
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Curvature and Velocity in Two-Dimensional Smooth Pursuit Eye Movements

Abstract: Curvature and tangential velocity of voluntary hand movements are constrained by an empirical relation known as the TwoThirds Power Law. It has been argued that the law reflects the working of central control mechanisms, but it is not known whether these mechanisms are specific to the hand or shared also by other types of movement. Three experiments tested whether the power law applies to the smooth pursuit movements of the eye, which are controlled by distinct neural motor structures and a peculiar set of mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(82 citation statements)
references
References 57 publications
6
74
2
Order By: Relevance
“…The other not perfect result, i.e., the 2/3rd power law, can be related with the nature of trajectories, which are not oscillatory (circles, ellipses, Lissajous figures, etc.) as in the papers, which observed first the phenomenon (de'Sperati and Viviani, 1997). The boundary effects (also related to initial and final speed and curvature) can have indeed a strong influence on the results, which indeed do not depend on the human likeness of the trajectories.…”
Section: Discussionsupporting
confidence: 69%
“…The other not perfect result, i.e., the 2/3rd power law, can be related with the nature of trajectories, which are not oscillatory (circles, ellipses, Lissajous figures, etc.) as in the papers, which observed first the phenomenon (de'Sperati and Viviani, 1997). The boundary effects (also related to initial and final speed and curvature) can have indeed a strong influence on the results, which indeed do not depend on the human likeness of the trajectories.…”
Section: Discussionsupporting
confidence: 69%
“…The same dimensionless representation may also be useful in analyzing other scale-invariant features and reveal spectrum of power laws in other motor contexts. Power laws have indeed been observed in many types of movements, including 3D hand movements (16), smooth pursuit eye movements (17), speech (18), and walking (19), and also appear in visual motion perception (20).…”
Section: Discussionmentioning
confidence: 92%
“…Since the original demonstration, it has been reported that the law also applies to different types of motion, such as tongue movements during speech (Tasko and Westbury 2002;Perrier and Fuchs 2008), locomotive trajectories (Vieilledent et al 2001;Ivanenko et al 2002;Hicheur et al 2005;Pham et al 2007), and smooth eye movements (de'Sperati and Viviani 1997). It was also found that the Abstract Several types of continuous human movements comply with the so-called Two-Thirds Power Law (2/3-PL) stating that velocity (V) is a power function of the radius of curvature (R) of the endpoint trajectory.…”
Section: Showed That V(t) Is Approximately Proportional To the Cubic mentioning
confidence: 99%